Kinetic modeling of propylene homopolymerization in a gas-phase fluidized-bed reactor - Shamiri, A.; Hussain, Mohd Azlan; Mjalli, F.S.; Mostoufi, N. (Elsevier, 2010)
A comprehensive mechanistic model describing gas-phase propylene polymerization is developed. The kinetics of polymerization is based on a multiple active site for Ziegler-Natta catalyst. The model considers the polymerization reaction to take place in both bubble and emulsion phases. The developed model was used to predict polymer production rate, number and weight average molecular weights, polydispersity index (PDI) and melt flow index (MFI). Results showed that by increasing the superficial gas velocity from 0.1 to 0.7 m/s the proportion of the polymer produced in the bubble phase increases from 7.92 to 13.14 which highlights the importance of considering the existence of catalyst in the bubble phase. Comparing the developed model with published models of the same reactor revealed that the polymer productivity will be higher using the new model at high catalyst feed rate.